Inequality and Labor Market Institutions - Jaumotte, Florence (Staff Discussion Notes; Staff Discussion Notes, 2015)
The SDN examines the role of labor market institutions in the rise of income inequality in advanced economies, alongside other determinants. The evidence strongly indicates that de-unionization is associated with rising top earners' income shares and less redistribution, while eroding minimum wages are related to increases in overall income inequality. The results, however, also suggest that a lack of representativeness of unions may be associated with higher inequality. These findings do not necessarily constitute a blanket recommendation for higher unionization and minimum wages, as country-specific circumstances and potential trade-offs with other policy objectives need to be considered. Addressing inequality also requires a multipronged approach, which should include taxation reform and curbing excesses associated with financial deregulation.